Correction of the torso position of female sprinter athletes based on changes in postural balance - Vinogradova O.P.; Morozova L.V.; Melnikova T.I.; Poniasov O.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to provide a methodological substantiation of the effect of postural balance on the correction of the body position of an athlete when covering a distance. Methods and structure of the study. Generalization and interpretation of established axioms in the training of female sprinters justified the need to conduct a pedagogical experiment using the proposed methodology, the basis of which was adapted means from fitness programs using a Bosu platform for the development of postural balance and functional TRX loops for strengthening stabilizer muscles. Results and conclusions. The effectiveness of the technique was confirmed by statistically significant differences in the results of running 60 m before and after the experiment. It has been established that exercises on TRX loops, a bosu platform and a fitball contribute to the development of coordination abilities and the ability to control the body in space, both in a supported and unsupported position. Positive dynamics of statokinetic indicators in female sprinters was achieved through targeted improvement of postural balance and increasing the strength potential of the muscles that ensure the maintenance of static and dynamic balance.